Error-Related Negativity and the Misattribution of State-Anxiety Following Errors: On the Reproducibility of Inzlicht and Al-Khindi (2012) - Cano Rodilla, Carmen; Beauducel, André; Leue, Anja (Frontiers in Human Neuroscience, 2016)
In their innovative study, Inzlicht and Al-Khindi (2012) demonstrated that participants who were allowed to misattribute their arousal and negative affect induced by errors to a placebo beverage had a reduced error-related negativity (ERN/Ne) compared to controls not being allowed to misattribute their arousal following errors. These results contribute to the ongoing debate that affect and motivation are interwoven with the cognitive processing of errors. Evidence that the misattribution of negative affect modulates the ERN/Ne is essential for understanding the mechanisms behind ERN/Ne. Therefore, and because of the growing debate on reproducibility of empirical findings, we aimed at replicating the misattribution effects on the ERN/Ne in a go/nogo task. Students were randomly assigned to a misattribution group (n = 48) or a control group (n = 51). Participants of the misattribution group consumed a beverage said to have side effects that would increase their physiological arousal, so that they could misattribute the negative affect induced by errors to the beverage. Participants of the control group correctly believed that the beverage had no side effects. As Inzlicht and Al-Khindi (2012), we did not observe performance differences between both groups. However, ERN/Ne differences between misattribution and control group could not be replicated, although the statistical power of the replication study was high. Evidence regarding the replication of performance and the non-replication of ERN/Ne findings was confirmed by Bayesian statistics.